Google Cloud Platform (GCP) Certification Associate Cloud Engineer 2020 - Colyer, Nick (Skylines Academy, LLC, 2020)
Welcome to the NEW Skylines Academy GCP Associate Cloud Engineer 2020 course! The cloud computing market is one of the fastest growing with some of the most in-demand skillsets today. With the realization that people need to get up-to-speed on how to administer and develop services with Google Cloud Platform (GCP), Google has a full portfolio of certifications which can now be achieved by IT professionals. In the GCP Certification Course: Associate Cloud Engineer, you will learn how to effectively manage GCP solutions and deploy apps, all while monitoring your operations. During your journey, Skylines Academy will lead you through a series of sections, lectures, and demos to prepare you for taking, and ultimately passing, the GCP Associate Cloud Engineer exam. Lectures will educate you on the fundamental terms and principles of GCP and demos will enable you with a hands-on experience using scenarios to empower you in the real world. What you will learn: Know how to implement infrastructure solutions in GCP What you need to pass the GCP Associate Cloud Engineer Certification Exam Core GCP fundamentals Get started on your journey to becoming a GCP Associate Cloud Engineer Course Requirements: You should have a foundational knowledge cloud computing concepts: network, storage, compute, etc. You do not need to know any specific code. Course Curriculum: Course Introduction Cloud Computing Introduction Google Cloud Overview Project Accounts and Billing Identity and Access Management (IAM) Networking Google Compute Engine Google App Engine Storage and Database Services Automation with GCP This course includes all the information you need to accelerate your learning in the most efficient way possible. So what are you waiting for? Sign up today and get ahead with GCP!